Faktor Penentu Minat Mahasiswa Akuntansi Indonesia Berkarir di Kantor Akuntan Publik - Wardani, Dewi Kusuma; Nuraini, Nuraini; Angelina, Tiara (Universitas Hamzanwadi, 2024)
Previous studies on accounting students' interest in a career in PAF only analyzed the direct relationship between accounting knowledge, job market, and financial rewards, without considering the moderating effect of financial rewards. This study investigates the relationship between accounting knowledge and job market considerations on interest in a career in PAF and the role of financial rewards as moderation. Quantitative method and snowball sampling were used in this study with 151 accounting student respondents in Indonesia. Research analysis through moderated regression analysis. The findings of this study are that accounting knowledge has a negative effect, while interest in working at KAP increases as a result of labor market considerations. Financial rewards weaken the impact of accounting knowledge and strengthen the influence of labor market considerations. Accounting knowledge and positive labor market considerations are expected to encourage career interest in PAF, especially with the support of financial rewards